Relationship between Selected Factors and Operation of Local Health Insurance Fund Board, Angthong Province - Sittichok, Wuttichai; Sumpowthong, Kaysorn (Journal of Health Science of Thailand, 2017)
This research aimed to study the relationship between personal factors, knowledge, attitude, per-ceived roles, self-efficacy and the operations of local health insurance fund boards in Angthong Province. The study samples were 235 members of 17 fund boards randomly selected from 64 local health insurance in Angthong Province during 2013. Data were collected by using questionnaires. Descriptive statistics such as number, percentage, mean and standard deviation were applied. Chi-Square test and correlation analysis were used to identify the relationships between those variables. The results of this study showed that most of samples was male aged between 40-60 years old with working experience of 1-4 years. Their knowledge, attitude, perceived roles, self-efficacy and operations of local health insurance fund board were at high levels. The personal factors including position in the local health insurance fund board and working experiences were associated with the operation of local health insurance fund boards. The attitude, perceived roles and self-efficacy were sigificantly associated with the efficient operation of the local health insurance fund boards (p<0.05).